On particles in the Arctic stratosphere - Jørgensen, T. S. (INGV, 2003)
Soon after the discovery of the Antarctic ozone hole it became clear that particles in the polar stratosphere had an infl uence on the destruction of the ozone layer. Two major types of particles, sulphate aerosols and Polar Stratospheric Clouds (PSCs), provide the surfaces where fast heterogeneous chemical reactions convert inactive halogen reservoir species into potentially ozone-destroying radicals. Lidar measurements have been used to classify the PSCs. Following the Mt. Pinatubo eruption in June 1991 it was found that the Arctic stratosphere was loaded with aerosols, and that aerosols observed with lidar and ozone observed with ozone sondes displayed a layered structure, and that the aerosol and ozone contents in the layers frequently appeared to be negatively correlated. The layered structure was probably due to modulation induced by the dynamics at the edge of the polar vortex. Lidar observations of the Mt. Pinatubo aerosols were in several cases accompanied by balloon-borne backscatter soundings, whereby backscatter measurements in three different wavelengths made it possible to obtain information about the particle sizes. An investigation of the infl uence of synoptic temperature histories on the physical properties of PSC particles has shown that most of the liquid type 1b particles were observed in the process of an ongoing, relatively fast, and continuous cooling from temperatures clearly above the nitric acid trihydrate condensation temperature (TNAT). On the other hand, it appeared that a relatively long period, with a duration of at least 1-2 days, at temperatures below TNAT provide the conditions which may lead to the production of solid type 1a PSCs. Published JCR Journal open